Non-linear thermoelastic analysis of steel arch members subjected to fire - Amin, Heidarpour; Abdul Azim, Abdullah; Mark A., Bradford (Elsevier Ltd., 2010)
This paper addresses the non-linear thermoelastic behaviour of steel arches acted on by a sustained uniformly distributed load, when subjected to elevated temperatures as caused by fire. The steel arch is restrained at its two ends by elastic translational springs in both the horizontal and vertical directions,as well as by counterpart elastic rotational springs, which simulate a generic semi-rigid connection, or restraint by other members in a frame, or when the arch acts as a large-span roofing element supported and restrained by columns. The study is restricted to the thermoelastic structural response of the steel material and therefore the high-temperature effects of catenary action and yielding are not considered;however the important effect of the second order term in the strain–displacement relationship is included. In order to model structural response of an elastically supported steel arch under thermal loading, an alternative geometric formulation is needed since the tangential and radial deflections and rotations as well as the axial compressive force in the member are substantial at the early stage of the fire. The formulation presented in this paper takes into account the degradation of the stiffness of the steel arch prior to yielding at elevated temperatures and it is argued that there are many situations for which analyses of a real fire situation in the thermoelastic range are valid. It is shown that the proposed model agrees well with independent solutions obtained using finite element analyses. The proposed model has significant potential for use in the analysis of restrained steel arches subjected to uniformly distributed load at elevated temperatures, such as large-span roofs and can provide a foundation for codified procedures in design.